The effect of some family characteristics on the relationship between mental symptoms and levels of serum serotonin and salivatory cortisol - MADEN, Özgür; UZUN, Özcan (Journal of health sciences and medicine : (Turkey), 2023)
Aim: Psychological symptoms (PSs) are also seen in healthy individuals. The aim of this study is to examine some familial features in the relationship between PSs and serum serotonin (5-HT) and salivary cortisol (CTS) levels in healthy subjects. Materials and Method: Sociodemographic data form and psychiatric symptom screening questionnaire (SCL-90-R) were given to 320 healthy individuals (156 males, 164 females) aged 18-65 without any mental illness. Blood and saliva samples were duly taken and evaluated by ELISA method. Informed consent and local ethics committee approval were obtained from the participants before starting the study. Statistical analyzes were done with SPSS 15.0 program. Descriptive statistical data (number, percentage, mean, standard deviation, minimum and maximum), independent sample t-test, One-way ANOVA test, Pearson Correlation analysis were used in the analyzes. For statistical significance, p<.05 was accetted significant.Results: The mean age of the participants was 29.19±8.41. According to family characteristics, PSs were found to be higher in those whose parents were separated, whose parents had a low educational level, and those with a family history of psychiatric illness. Depressive symptoms were statistically significantly higher in those whose families were separated. Somatization, anxiety, obsessive symptoms, depressive symptoms, hostility and additional symptoms were statistically significantly higher in those with a family history of psychiatric illness. Although it was not statistically significant, the 5-HT levels were highest in those living in an extended family, those whose parents lived together, those whose parents were primary school graduates, and those who did not have a family history of psychiatric disease. CTS levels were statistically significantly higher in those who did not have a family history of psychiatric disease. There was a negative correlation between 5-HT and CTS levels and PSs excluding additional symptoms. There was a positive correlation between 5-HT and CTS levels.Conclusion: It was concluded that familial characteristics have an effect on the relationship between psychological symptoms and serotonin and cortisol levels in healthy individuals, but these characteristics alone are not effective in this relationship. There is a need for studies investigating other stressor factors that are thought to be effective in the relationship between mental symptoms and serotonin and cortisol levels.